PENGARUH ANGKAK HASIL FERMENTASI BERAS OLEH Monascus purpureus JMBa TERHADAP AKTIVITAS ANTIOKSIDAN DAN GLUTATHION PEROKSIDASE (GPx) SERTA HISTOPATOLOGI HATI TIKUS GALUR SPRAGUE DAWLEY - Ernawati Kasim; Evi Triana; Titin Yulinery; Novik Nurhidayat (BERITA BIOLOGI, 2012)
Free radicals released from metabolism processes in the body were reactive and toxic to cells and tissues because it cause protein, cell membrane and nucleic acid damages which lead to cancer. It could be overcame if antioxidant system in the body is in good function.Nevertheles antioxidant system could be destructed by variety of conditions. Modern lifestyle that frequently consumed of high saturated fat, additives, and low fiber content in foods were potential risk for cancer and hypercholesterolemia. To overcome that risks with specific drugs were high cost. Therefore this research was conducted to take advantages of natural sources which potential for antioxidant and antihypercholesterolemia activities that could be fast, easy and inexpensive processing. One of the natural sources that meet the criteria was angkak resulted from rice fermented by Monascus purpureus. The result revealed that angkak contained lovastatin showed antioxidant and antihypercholesterolemia activities and increased glutathion peroxidase activity of optimal dose 5 g/day. The histopathologi observation of rat’s liver showed that administered of angkak on rats feed high level of cholesterol inhibited accumulation of fat in rat’s liver.